2023
DOI: 10.3390/su151914240
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Technological Innovation on Environment, Social, and Governance (ESG) Performance and Firm Value: Evidence from Developing and Least-Developed Countries

Yusheng Kong,
Andrew Agyemang,
Noha Alessa
et al.

Abstract: Recently, there has been growing recognition of the significance of environmental, social, and governance (ESG) factors in assessing a company’s performance and worth. Previous research has failed to take into account the significant impact of technological innovation in their empirical investigations. This study fills the gap by investigating the moderating impact of technological innovation on ESG performance and company value in developing and least-developed countries. The study utilized secondary data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…For example, Mardini [125] shows that the company's performance is positively affected by governance and environmental factors, while it is negatively affected by social factors. Kong et al [126] indicated that governance does not affect firm value, while environmental and social performance have a positive effect. Gregory et al [127] argue that companies' adoption of their ESG responsibilities is evidence of their commitment to their social duties imposed by the government and society.…”
Section: Esg Clustermentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Mardini [125] shows that the company's performance is positively affected by governance and environmental factors, while it is negatively affected by social factors. Kong et al [126] indicated that governance does not affect firm value, while environmental and social performance have a positive effect. Gregory et al [127] argue that companies' adoption of their ESG responsibilities is evidence of their commitment to their social duties imposed by the government and society.…”
Section: Esg Clustermentioning
confidence: 99%
“…Khalil et al [141] divided innovation into two parts: an important environmental innovation that enhances the company's value and a traditional innovation that negatively affects the firm's value as a result of activating carbon emissions, which affects ESG performance. Kong et al [126] showed that innovation works as a catalyst in improving the relationship between ESG performance and firm value, which contributes to implementing practices with high efficiency and achieving sustainability. Finally, it can be said that innovation contributes to improving the role that ESG performance plays in adding value to firms, especially in light of rapid environmental changes and facing sudden crises such as COVID-19.…”
Section: Innovation Clustermentioning
confidence: 99%
“…This study adopted and modified a model by [50] due to its relevance in exploring the connection between sustainability disclosures and financial performance. The following is the presentation of this model, which has strong empirical support and serves as a solid framework for this study:…”
Section: Model Specificationmentioning
confidence: 99%
“…In addition, some scholars have separately discussed the economic consequences of the three dimensions of ESG performance. Kong [28] believed that environmental and social performance affect firm value, but governance performance does not. Li [29] found that environmental factors are the most important factor in China's green finance investment decisions, followed by governance and social factors.…”
Section: Economic Effects Of Esgmentioning
confidence: 99%